Hematological Phenotype of COVID-19-Induced Coagulopathy: Far from Typical Sepsis-Induced Coagulopathy - Umemura, Yutaka (J Clin Med, 2020)
Background: Blood coagulation disorders commonly occur with severe coronavirus disease 2019 (COVID-19). However, there is only limited evidence on differentiating the pattern of the hemostatic parameters from those of typical sepsis-induced coagulopathy (SIC). Methods: To elucidate the specific pattern of coagulopathy induced by COVID-19 pneumonia, this retrospective, observational study targeted consecutive adult patients with COVID-19-induced acute respiratory distress syndrome (ARDS) and compared hemostatic biomarkers with non-COVID-19-induced septic ARDS. Multilevel mixed-effects regression analysis was performed and Kaplan–Meier failure curves were constructed. Results: We enrolled 24 patients with COVID-19-induced ARDS and 200 patients with non-COVID-19-induced ARDS. Platelet count, antithrombin activity, and prothrombin time in the COVID-19 group were almost within normal range and time series alterations of these markers were significantly milder than the non-COVID-19 group (p = 0.052, 0.037, and 0.005, respectively). However, fibrin/fibrinogen degradation product and D-dimer were significantly higher in the COVID-19 group (p = 0.001, 0.002, respectively). COVID-19 patients had moderately high levels of thrombin–antithrombin complex and plasmin-alpha2-plasmin inhibitor complex but normal plasminogen activator inhibitor-1 level. Conclusions: The hematological phenotype of COVID-19-induced coagulopathy is quite different from that in typical SIC characterized by systemic hypercoagulation and suppressed fibrinolysis. Instead, local thrombus formation might be promoted in severe COVID-19.